2015
DOI: 10.1038/ejcn.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

Length and weight of very low birth weight infants in Germany at 2 years of age: does it matter at what age they start complementary food?

Abstract: VLBW infants are introduced to complementary food on average before a post-term age of 4 months. There was no negative effect of early introduction of complementary food on height and weight at 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 16 publications
3
28
0
1
Order By: Relevance
“…They found that for each month the infants received complementary food later, the Z-score for length (cm) and weight (kg) was reduced by –0.1 at the age of 2 years, leading to the conclusion that the infants appeared to benefit from the early introduction of complementary feeding [26]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that for each month the infants received complementary food later, the Z-score for length (cm) and weight (kg) was reduced by –0.1 at the age of 2 years, leading to the conclusion that the infants appeared to benefit from the early introduction of complementary feeding [26]. …”
Section: Resultsmentioning
confidence: 99%
“…The prospective observational study of Spiegler et al [26] reported growth in length and weight using Percentiles of Rosario and calculated Z-scores with a follow-up time of 24 months [27]. They found that for each month the infants received complementary food later, the Z-score for length (cm) and weight (kg) was reduced by –0.1 at the age of 2 years, leading to the conclusion that the infants appeared to benefit from the early introduction of complementary feeding [26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations